Historical discourse and national narratives - G.K. Gizatova; O.G. Ivanova (Ученые записки Казанского университета: Серия Гуманитарные науки)
A correlation between historical discourse and ethnic narratives was analyzed. The most important feature of a narrative is its inextricable relationship with socio-historical conditions: it is not only determined by a specific sociocultural context, but also acts as an important element of the constantly changing cultural and historical reality. Hence, the study of a relationship between the historical knowledge and national narrative as the most important component of national consciousness is of high practical relevance. The obtained results show that narratives, including national ones, serve as a mediator, a link between the past and the future. They are the genetic component of any national consciousness, reconstructing the national memory, carrying out a retrospective reflection of the past. National narratives are a special object of historical knowledge. One of the features of a narrative is that it does not represent historical facts directly, but often symbolically. In national narratives, their figurative nature, a system of multilevel coding, enclosed in the text, is manifested in all distinctness. Therefore, the relationship of historical discourse and national narrative is always manifested through the language, within which and with the help of which meanings are produced. The key to understanding the interpretation of the past is always in the culture. With regard to national narratives, it is the national culture that spawns its own ways of encoding and decoding meanings.